2013
DOI: 10.2172/1074191
|View full text |Cite
|
Sign up to set email alerts
|

On The Lack of Time Dilation Signatures in Gamma-ray Burst Light Curves

Abstract: We examine the effects of time dilation on the temporal profiles of gamma-ray burst (GRB) pulses. By using prescriptions for the shape and evolution of prompt gamma-ray spectra, we can generate a simulated population of single pulsed GRBs at a variety of redshifts and observe how their light curves would appear to a gamma-ray detector here on Earth. We find that the observer frame duration of individual pulses does not increase with redshift as 1 = z that one would expect from the cosmological expansion. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…However, a recent study of over 800 quasar light curves found no evidence of the expected effects of time dilation [2]. This is a very surprising result with no explanation within the conventional cosmological framework (note that some studies report the lack of time dilation signatures also in gamma-ray burst light curves [29,30]. See however [31,32]).…”
Section: Space Expansion and Enigma Of Time Non-dilation In Quasar Li...mentioning
confidence: 88%
“…However, a recent study of over 800 quasar light curves found no evidence of the expected effects of time dilation [2]. This is a very surprising result with no explanation within the conventional cosmological framework (note that some studies report the lack of time dilation signatures also in gamma-ray burst light curves [29,30]. See however [31,32]).…”
Section: Space Expansion and Enigma Of Time Non-dilation In Quasar Li...mentioning
confidence: 88%
“…However, no such time dilation was found in the light curves of quasars [97,98] or in duration measures of GRBs [99,100], casting doubts on a key prediction of Lemaitre cosmologies, namely, the generality of the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…It has been claimed that, as predicted by Lemaitre cosmologies [31,32,33], the light curves of Type Ia supernovae are dilated by (1 + z) [34,35,36] and that, as a consequence, theories in which photons dissipate their energy during travel are excluded [34,35]. However, no such time dilation was detected in GRB [37] or quasar [38,39] light curves, casting doubts on the generality of the phenomenon.…”
Section: Discussionmentioning
confidence: 99%